General and Specific Combining Ability Estimates for Morphological, Yield and its Attributes and Seed Traits in Sunflower (Helianthus annuus L.): Sunflower Hybrids Study (Biological Sciences - PJSIR, 2018)
The improvement in sunflower breeding requires exploitation of combining ability of divergent male and female inbreds. Six cytoplasmic male sterile (CMS) lines and three testers were crossed in line ´ tester  design, thus 18 F1 hybrids were developed for evaluation of  general combining ability (GCA) and specific combining ability (SCA) of inbred parents for days to 90% maturity, stem girth, head size, achenes/plant, 1000-seed weight, achene yield kg/ha, oil and  protein%. The significant variances due to lines and testers both determined GCA variances revealed the predominance of additive genes whilst significance of lines ´ tester interactions indicated the importance of SCA variances and the involvement of non-additive genes in the expression of traits studied. The foremost role of non-additive genes was apparent when ratio s2 SCA/s2GCA was above 1.0. These results suggested the prevalence of dominant genes and possibility of hybrid crop development. The GCA effects indicated that CMS parents SF-187, 64-A-93 and ARG-0405 and tester RHP-46 were high general combiners, thus may be chosen for crossing  and  selection programmes, whereas F1 hybrids SF-187 ´ RHP-46, 64-A-93 ´ RHP-46, PAC-ARG-0405   PAC-ARG-0106, 64-A-93 ´ RHP-46 and PSF-025 ´ RHP-64 which used parents with good ´ good and good ´ poor GCA estimates revealed higher positive SCA estimates for achene yield, oil and protein traits yet manifested desirable negative effects for 90% maturity. Such results suggested that these hybrids are desirable for the exploitation of hybrid crop development or selection of desirable plants from earlier filial generations.